2018
DOI: 10.18203/2349-2902.isj20184636
|View full text |Cite
|
Sign up to set email alerts
|

Upper limb lymphedema related to breast cancer therapy: incidence, risk factors, diagnostic techniques, risk reduction and optimal management

Abstract: Background: Lymphedema remains to be a great source of morbidity for breast cancer survivors. The aim of this work is to study upper limb lymphedema following breast cancer therapy for breast cancer patients regarding its incidence, risk factors, diagnostic techniques, risk reduction and optimal management.Methods: This prospective study was done on two hundred breast cancer patients who underwent breast cancer management. The study was done in the period between May 2016 and July 2018. Exclusion criteria were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
(25 reference statements)
3
7
0
Order By: Relevance
“…2). This agrees with Babiker et al, (2020) and Saleh et al, (2018). Also, Juneja et al, (2019) they found the majority of breast cancer cases are in this age group.…”
Section: Discussionsupporting
confidence: 80%
“…2). This agrees with Babiker et al, (2020) and Saleh et al, (2018). Also, Juneja et al, (2019) they found the majority of breast cancer cases are in this age group.…”
Section: Discussionsupporting
confidence: 80%
“…The age 30-45years was the most frequent age group 48.6% (17/35), followed by 46-60 years 40% (14/35). This agrees with Hamad et al [9], Babiker et al [10], Saleh et al [11], Juneja et al [12], who found the majority of breast cancer cases are in this age group.…”
Section: Discussionsupporting
confidence: 91%
“…The study showed the majority of samples were grade III, 74.3% (26/35) and the samples of grade II were 25.7% (9/35). This agrees with Hamad et al [11], Galvez et al, [13] and Sundquist et al [14].…”
Section: Discussionsupporting
confidence: 91%
“…Seroma has also been associated with chronic BCRL 18‐22 . Comorbidities such as age, body mass index (BMI), hypertension, and diabetes have been evaluated as risks factors for chronic BCRL with mixed results 23‐30 . Finally, lifestyle behaviors such as smoking, air travel, and area of residence may also influence chronic BCRL risk 31‐36 .…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22] Comorbidities such as age, body mass index (BMI), hypertension, and diabetes have been evaluated as risks factors for chronic BCRL with mixed results. [23][24][25][26][27][28][29][30] Finally, lifestyle behaviors such as smoking, air travel, and area of residence may also influence chronic BCRL risk. [31][32][33][34][35][36] Available literature regarding smoking is scant.…”
Section: Introductionmentioning
confidence: 99%